Analisis Strategi Pemasaran untuk Meningkatkan Penjualan PT Poci Kreasi Mandiri di Kota Bogor - Veralianta Br Sebayang; Tasya Angelita; Agtris Herlinawati; Fastabiqul Khairat; Glori S Napitupulu; Rachel Sofia Audina; Rachmawati Rezeki Utami; Reindra Rahman (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
Marketing meets consumer needs and desires by involving social processes that include the creation and exchange of products and values. This research examines the marketing strategy for Teh Poci products managed by PT Poci Kreasi Mandiri, aiming to identify, evaluate, and formulate priorities for an appropriate marketing mix strategy. This study applies the Analytic Hierarchy Process (AHP) method to determine a priority from various options, focusing on identifying the marketing mix strategy (4P) already implemented by PT Poci Kreasi Mandiri, evaluating consumer perceptions of these strategies, and formulating suitable priorities for future marketing mix strategies. The analysis reveals that promotion is the primary aspect needing improvement, particularly through collaborations with relevant parties. Direct distribution is also identified as a critical second priority to expand market reach. Product variety should receive further attention to enhance consumer appeal, and the pricing aspect, especially regarding cup sizes, should be adjusted for optimal profit. The findings provide insights into marketing strategies that can support PT Poci Kreasi Mandiri in Bogor City in increasing sales of Teh Poci products.